2008
DOI: 10.1089/dia.2008.0016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Emerging Sensor Technologies in Diabetes Management: Consensus Guidelines for Continuous Glucose Monitoring (CGM)

Abstract: Continuous glucose monitoring (CGM) is an evolving technology poised to redefine current concepts of glycemic control and optimal diabetes management. To date, there are few randomized studies examining how to most effectively use this new tool. Therefore, a group of eight diabetes specialists heard presentations on continuous glucose sensor technology and then discussed their experience with CGM in order to identify fundamental considerations, objectives, and methods for applying this technology in clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 29 publications
0
88
0
1
Order By: Relevance
“…Insulin doses were increased for arrows going up and decreased for arrows going down as clinically indicated. 9 Finally, each period was simulated five times to present several random sensor profiles to each observed clinical situation, leading to 10,410 episodes for each noise level using each treatment modality with and without trend arrows, for a total of 437,220 simulations.…”
Section: Replay Of Observed Treatment Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin doses were increased for arrows going up and decreased for arrows going down as clinically indicated. 9 Finally, each period was simulated five times to present several random sensor profiles to each observed clinical situation, leading to 10,410 episodes for each noise level using each treatment modality with and without trend arrows, for a total of 437,220 simulations.…”
Section: Replay Of Observed Treatment Scenariosmentioning
confidence: 99%
“…Since the advent of CGM technology, 1-3 significant progress has been made toward versatile and reliable devices that not only approximate the course of blood glucose (BG) fluctuations day and night, but also provide feedback such as alarms when preset low or high thresholds are reached. Several studies have documented the benefits of CGM [4][5][6][7] and charted guidelines for its clinical use 8,9 and for its future as a base for closed-loop control. 10,11 Physiology and CGM errors…”
Section: Introductionmentioning
confidence: 99%
“…Permanent use of the Guardian RT device for 3 months significantly improved HbA 1c levels compared with SMBG, while intermittent CGM use showed no significant benefit [6]. The recent Juvenile Diabetes Research Foundation (JDRF) trial reported that CGM for 6 months led to significant HbA 1c improvement vs SMBG use only in young patients who showed good compliance with sensor use [16], although the incidence of severe or biochemical hypoglycaemic events was not significantly altered.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the increasing availability of continuous glucose monitoring (CGM) is helpful in detecting hyperand hypoglycaemic deviations that might otherwise go unrecognized with self-monitoring of blood glucose (SMBG) only [6]. Until now, the demonstrated benefits of CGM have focused on reducing HbA 1c in patients who were far from achieving their targeted HbA 1c levels [7,8], while outcomes of CGM use on the occurrence of hypoglycaemia have been poorly investigated and for short time-periods only [9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the "gold standard" is considered the mean amplitude of glycemic excursions (MAGE) value which is obtained by measuring the arithmetic mean of the differences between consecutive peaks and nadirs with a measurement in the peaks-to-nadir direction by the first qualifying excursion (Monnier et al 2007). MAGE estimation requires the use of new devices allowing continuous glucose monitoring on ambulatory basis (Hirsch et al 2008).…”
mentioning
confidence: 99%